Influence of nutritional factors and the PON1 C(-107)T polymorphism on paraoxonase-1 activity in childhood - Tainá S. Sigales; Gabriela Uliano; Ludmila Muniz; Carlos Barros; Augusto Schneider; Sandra C. Valle (Elsevier, 2020)
Objective: The cardioprotective enzyme paraoxonase-1 (PON1) suffers an important influence from genetic polymorphisms and nutritional factors. The aim of this study was to investigate the influence of diet, nutritional status, and the C(-107)T polymorphism on PON1 arylesterase activity in children. Methods: This was a cross-sectional study with 97 children, aged between 5 and 8 years, of both genders, from a pediatric outpatient clinic in southern Brazil. A sociodemographic, behavioral, and food consumption questionnaire was applied, and anthropometric measurements and laboratory blood samples were taken. PON1 arylesterase activity was measured by phenol extinction (U/mL), and DNA extraction and analysis of the PON1 C(-107)T polymorphism were performed. The Hardy-Weinberg equilibrium was tested with the chi-squared test and linear regression was used to estimate PON1 activity according to four adjustment models, with an acceptable error of 5%. Results: In the sample, the male gender accounted for 50.5%, 39.2% were 6 years of age, 54.5% had normal weight, and 51.5% had PON1 activity below the median (90.0, 15-30 U/mL). Genotype frequency was 54.6% (53/97), 31.0% (30/97), and 14.4% (14/97), respectively, for CT, CC, and TT, consistent with the Hardy-Weinberg equilibrium (p = 0.22). In the regression analysis, the model that included sociodemographic variables as well as frequency of consumption of fruits, vegetables, legumes, dairy products, and beans estimated a variability of 14.8% in PON1 activity combined with the PON1 C(-107)T polymorphism. Conclusions: During childhood, a good-quality diet with greater inclusion of healthy foods was important to predict the activity of the cardioprotective enzyme PON1 combined with the C(-107)T polymorphism of the PON1 gene. Resumo: Objetivo: A enzima cardioprotetora Paraoxonase 1 (PON1) sofre importante influência de polimorfismos genéticos e fatores nutricionais. O objetivo deste estudo foi investigar a influência da alimentação, do estado nutricional e do polimorfismo C(-107)T sobre a atividade arilesterase da PON1 em crianças. Métodos: Estudo transversal com 97 crianças entre 5 e 8 anos, de ambos os sexos, de um ambulatório de pediatria no sul do Brasil. Realizou-se questionário sociodemográfico, de comportamento e de consumo alimentar, medidas antropométricas e coleta de sangue em laboratório. A atividade arilesterase da PON1 foi mensurada pela extinção de fenol (U/mL), realizada extração do DNA e análise do polimorfismo PON1 C(-107)T. O equilíbrio de Hardy-Weinberg foi testado com qui-quadrado e usada regressão linear para estimar a atividade da PON1 segundo quatro modelos de ajuste, erro aceitável de 5%. Resultados: Na amostra o sexo masculino representou 50,5%, 39,2% tinham 6 anos, 54,5% eram eutróficos e 51,5% tinha atividade da PON1 inferior à mediana (90,0;15-30 U/ml). A frequência dos genótipos foi 54,6% (53/97), 31,0% (30/97) e 14,4% (14/97), respectivamente, para CT, CC e TT, estiveram em equilíbrio de Hardy-Weinberg (p = 0,22). Na análise de regressão o modelo que incluiu variáveis sociodemográficas, de frequência do consumo de frutas, verduras, legumes, laticínios e feijões estimou uma variabilidade de 14,8% na atividade da PON1 combinada ao polimorfismo PON1 C(-107)T. Conclusões: Na infância uma alimentação de boa qualidade, com maior participação de alimentos saudáveis foi importante para predizer a atividade da enzima cardioprotetora PON1 combinada ao polimorfismo C(-107)T do gene da PON1.